Digital Literacy and Cybersecurity for Teachers and Students in the Era of Hybrid and Virtual Education - Eni Setyo Rahayu (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
The transformation of education in the digital era has demanded the integration of digital literacy and cybersecurity as two fundamental aspects for the sustainability of hybrid and virtual learning systems. This study uses a qualitative approach with a literature review method that examines various academic sources, educational policies, and legal frameworks related to digital competency and data protection. The results of the study indicate that digital literacy functions as a basic capability encompassing technological, cognitive, and ethical dimensions, while cybersecurity plays a role as an instrument of legal protection for digital activities in the educational space. Teachers and students have a legal and moral responsibility to maintain information security, avoid privacy violations, and uphold the principles of academic integrity in the cyber environment. The discussion emphasizes the need for systematic integration of digital literacy and cybersecurity in national education policy to create a safe, inclusive, and sustainable learning ecosystem. Strengthening the digital legal capacity of educators and students is a strategic step in building a learning culture based on ethics, responsibility, and protection of digital rights. In conclusion, digital literacy and cybersecurity are not merely technological necessities, but normative foundations that guarantee the sustainability and legality of education in the global digital er